New floral records for the provinces of Mendoza and San Juan (Argentina) (Semiárida, 2018)
In february 2012 floral collections were made at Uspallata hills (Mendoza) and South Callingasta department (San Juan). Taxonomical identification from herborized plants and information searches in data bases allowed us to confirm the presence of Pastinaca sativa L. in San Juan province just like Hypochaeris tenerifolia (J. Rèmy) Dusén and Solanum tweedianum Hook. in Mendoza province.
Keywords: Mendoza; San Juan; Puna; Flora; New records